Bactericidal Effect against Helicobacter pylori and Chemical Profile of Booth Avocado Leaves Collected in Dak Lak Province - Thi Nhi Cong, Le; Dieu, Vu Duy; Linh, Nguyen Viet; Nga, Tran Thi Huyen; Dung, Nguyen Dinh Tien (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4DO - 10.25073/2588-1140/vnunst.5797, 2025)
Avocado is one of the most popular fruits in Vietnam, however, there are limited national publications concerning to bioactive compounds extracted from avocado leaves. Meanwhile, annually, after harvesting avocado fruits, a huge of leaves are cut off to prepare for the next season’s fruit production. This is an extremely abundant and unexploited material. Besides, according to the literatures, avocado leaf extracts contained a high amount of secondary metabolites, especially anthocyanin and mono-aromatic phenolic acid compounds, therefore, their bioactivities are diverse. For instance, the extracts could resist several kinds of bacteria, such as Helicobacter pylori, Micrococcus pyogenes var aureus , Escherichia coli, Burallus subritis . In the present study, the Booth avocado leaf extraction by distilled water, ethanol and hexane was conducted. The extracts were examined  for the capacity of H. pylori resistance. H. pylori is one of the dangerous bacterial species which could cause stomach ulcers. The results showed that hexane extracts had the highest ability of H. pylori resistance. The MIC was 71.5 mg/ml. According to gas chromatography mass spectra (GC/MS), the first structural analysis of the extract was proposed as apigenin with fragment ions m/e 270, 173, 145, 121, 105, and 94. The amount of apigenin was defined for the concentration range 0.02–0.1 mg/mL. The results gave a potential application of Booth avocado leaf to resist H. pylori and it could be used as a material for products to support stomach ulcers caused by H. pylori .